Monoclonal origin of localised orbital amyloidosis detected by molecular analysis. Issue 11 (November 1996) - Pasternak, S; White, V A; Gascoyne, R D; Perry, S R; Johnson, R L; Rootman, J
Abstract : AIMS: Primary localised orbital amyloidosis is a rare disease. The purpose of this study was to describe two cases of primary orbital amyloidosis and emphasise the value of molecular analysis of immunoglobulin gene rearrangement in identifying a monoclonal population of cells responsible for the amyloid production. METHODS: Charts and biopsy specimens of each case were reviewed. Conventional light microscopy, immunohistochemistry, and polymerase chain reaction (PCR) analysis for immunoglobulin gene rearrangement were performed in both cases. RESULTS: An unusual presentation of localised primary amyloidosis with bilateral and extensive enlargement of multiple extraocular muscles was seen in case 1. The presence of amyloid deposits was confirmed by biopsy in both cases. Evidence of a monoclonal population of plasma cells was shown by immunohistochemical analysis in case 2 only. The monoclonal origin of the cells responsible for the amyloid deposition was determined by PCR analysis demonstrating immunoglobulin heavy chain gene rearrangement in both cases. CONCLUSIONS: A monoclonal population of plasma cells responsible for the amyloid deposition was present in these two cases. PCR analysis is extremely helpful in determining monoclonality, a finding that may have important therapeutic and prognostic implications.